Teachers’ Conceptions and Uses of Interactive Spherical Video-based Virtual Reality in Teaching Chinese Writing (International Conference on Computers in Education, 2020)
This study integrates interactive spherical video-based virtual reality (ISV-VR) into Chinese descriptive composition education. This paper reports teachers’ conceptions of teaching with regards to the use of interactive spherical video-based virtual reality (ISV-VR) in Chinese descriptive composition writing. The findings may provide researchers and practitioners with novel insight into the teaching of composition writing in the contexts of first language acquisition supported by virtual reality technology.